Pergantian Dewan Komisaris Dan Dewan Direksi Terhadap Pengungkapan Laporan Keberlanjutan - Bunga Novitasari; Andi Manggala Putra; Akhmad Saebani (Wahana: Jurnal Ekonomi, Manajemen dan Akuntansi, 2021)
This study aims to examine the turnover of the board of commissioners, board of directors, audit committee, and independent board of directors on the disclosure of sustainability reports. In this study turnover was measured using member recruitment and member removal. The sample in this study amounted to 135 samples from 45 financial companies listed on the Indonesia Stock Exchange during the 2016-2018 period. The analysis technique used is panel data regression analysis using STATA 13. The results of this study found that the recruitment of the board of commissioners, the board of directors, and the audit committee have a significant effect on disclosure of sustainability reports. The recruitment of an independent board of directors has no significant effect on disclosure of sustainability reports. While the removals of board of commissioners and directors have no effect. This study provides a new understanding of corporate governance in which the recruitment of members of the board of commissioners and directors will affect the disclosure of corporate sustainability reports. This study uses a new measure, that is the recruitment and removal of members of the board of commissioners and directors.